2014
DOI: 10.4103/0971-9261.129608
|View full text |Cite
|
Sign up to set email alerts
|

Ex-utero intrapartum treatment in the Indian scenario: Anesthetic challenges and positioning

Abstract: Ex-utero intrapartum treatment (EXIT) is performed for fetuses diagnosed with large neck masses. A case report of a fetus diagnosed with a large cystic hygroma and cord around the neck who was delivered by EXIT is presented. The airway challenges and optimal positioning is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…EXIT procedure has been reviewed by many authors, and a case of cervical cystic hygroma with cord around the neck has been reported from India. [ 4 5 ] We describe the successful anesthetic management of an EXIT procedure for a fetus with antenatally diagnosed large anterior neck teratoma and present the literature review on perioperative management of such cases.…”
Section: Introductionmentioning
confidence: 99%
“…EXIT procedure has been reviewed by many authors, and a case of cervical cystic hygroma with cord around the neck has been reported from India. [ 4 5 ] We describe the successful anesthetic management of an EXIT procedure for a fetus with antenatally diagnosed large anterior neck teratoma and present the literature review on perioperative management of such cases.…”
Section: Introductionmentioning
confidence: 99%